Evolution Mechanism of Water-Conducting Channel of Collapse Column in Karst Mining Area of Southwest China - Zhengzheng Cao; Yulou Ren; Qinting Wang; Banghua Yao; Xinchao Zhang (Geofluids)
There are many karst collapse columns in coal seam roof in the southern coal field in China, which are different from those in coal seam floor in the northern coal field, due to the stratum characteristics. The karst collapse column in coal seam roof tends to reactivate and conduct water and induce the serious water inrush disaster, when the karst collapse column communicates with the overlying aquifer. In order to reveal the evolution mechanism of water-conducting channel of collapse column in karst mining area of southwest China, the aquifers and water inflow rule in 1908 working face in Qianjin coal mine are analyzed. Besides, the particle size distribution and mineral component of collapse column are researched by the X-ray diffraction test and the screening method, which are the basis for researching the water inrush mechanism in karst collapse column. On this basis, the water inrush of roof collapse column under the influence of mining is researched by establishing the numerical calculation model with the UDEC numerical software. The results show that the water flowing into the 1908 working face comes from the Changxing formation aquifer and Yulongshan formation aquifer above the coal seam, and the proportion of coarse particles and fine particles in collapse column is 89.86% and 10.14%, respectively. With the advance of working face, the water-conducting channel connected the working face with the aquifer, or the surface is formed by collapse pits, karst caves, and collapse column. The research results can be treated as an important basis for the water-preserved mining in southern coal field in China.